Digital Technology Access and Income Inequality: A Labour Market Behaviour Perspective in Rural Indonesia - Fitra Jaya; Romi Siswanto; Yati Yati; Kadarisman Kadarisman; Sucipto Sucipto (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
The importance of digital technology for inclusive economic development is becoming increasingly evident. This paper examines the impact of digital access and productive internet use on the individual labor income of rural Indonesians across different income percentiles, taking into account the heterogeneity of rural digital infrastructure and the high level of informality in the rural sector. By utilizing the 2024 National Socioeconomic Survey and the National Labour Force Survey, this paper employs the quantile regression technique to examine the effects of digital access and internet engagement at the 25th, 50th, and 75th income percentiles. The results indicate that digital access has a significant benefit for lower-middle-income individuals, with decreasing returns at higher income levels. Conversely, productive internet usage is associated with increased income, particularly at the upper quantiles, suggesting that digital skills enable rural individuals to capitalize on economic opportunities. Additionally, the proxies for job-searching behaviors do not demonstrate a relationship with income in any quantile, which indicates structural issues with the rural labor market. Thus, policymakers need integrated digital inclusion strategies that focus both on capability and institutional constraints to ensure fair economic access for rural residents.